Validation of the French Version of the Child Posttraumatic Stress Checklist in French School-Aged Children - Gindt, Morgane; Richez, Aurelien; Battista, Michèle; Fabre, Roxane; Thümmler, Susanne; Fernandez, Arnaud; Askenazy, Florence (Frontiers in Psychiatry, 2021)
Background: The child posttraumatic stress disorder checklist (CPC) updated to DSM-5 is a questionnaire aimed to assess posttraumatic stress disorder (PTSD) symptoms in children. It is available in both parents and child versions. The back-translation method has been used for the French translation of the CPC. It has not been yet validated in French-speaking populations. The aim of this study was to assess the psychometric properties and the validity of the CPC in a sample of French-speaking schoolchildren and their parents. Methods: The sample was composed by 176 children outpatients implicated in the Nice terrorist attack (14 July 2016) aged 7–17 (mean = 11.68 years, SD = 2.63 months) and 122 parents. Cronbach's alpha was used to test CPC internal consistency. The Spearman-correlation coefficient was performed between the French version of the CPC and the Kiddie Schedule for Affective Disorders and Schizophrenia Present and Lifetime version (K-SADS-PL) to assess the convergent validity. An ROC curve was constructed to verify the validity of the cutoff scores. An evaluation of the sensitivity and specificity of each score and a comparison with the diagnosis of the K-SADS-PL were made. Finally, a principal component analysis with varimax rotation was computed to analyze the structure of the French version of the CPC. Results: Cronbach's alpha coefficient was 0.90 for child version and 0.91 for parent version of the CPC. There was a statistical correlation between the K-SADS-PL for PTSD and the total score of CPC for the child version (r = 0.62; p < 0.001) and for the parent version (r = 0.55; p < 0.001). The sensitivity and specificity of the children version with a threshold of >20 were 73.1 and 84.7%, respectively, using the K-SADS-PL as the diagnostic reference for PTSD. Concerning the parent version, using the same recommended cutoff score, the sensitivity, and specificity were 77 and 80.5%, respectively. Conclusions: The psychometric properties of the French CPC are good. This questionnaire appears to be valid and should be used in French-speaking children.